STABILITY OF MANGANESE (II) CHLORIDE COMPLEXES FROM 25 TO 300OC - Gammons C.H.; Seward T.M. (My University, 1996)
The stability and stoichiometry of the Mn(II) chloride complexes have been experimentally determined in the temperature range 25 to 300°C. The solubility of AgCl(s) was measured in solutions of fixed HCl concentration (0.01-6.0 m) and varying ΣMnΣCl molar ratio (0.0-0.5), following a modification of the method of Ruaya and Seward (1986). The results were regressed to obtain the following smoothed values for the first and second cumulative association constants (β1 and β2, respectively) for the Mn(II) chloride complexes:Our study indicates that Mn2+ is the dominant species at 25oC, whereas the stabilities of MnCl+ and MnCl02 increase rapidly with temperature. In the absence of competing ligands, the neutral MnCl02 complex should dominate Mn transport for chloride-rich hydrothermal fluids at or above 300oC. No evidence was found for complexes of higher ligand number (e.g., MnCl-3, MnCl2-4). Our results indicate that Mn is more strongly complexed than Fe at elevated temperature.The solubilities of some common manganese-bearing minerals have been calculated as a function of pH, aCl-, ΣCO3, and temperature. The minerals rhodonite and rhodocrosite are highly soluble in mildly acidic solutions. Most active geothermal systems are, therefore, expected to be undersaturated with respect to these phases, although they may locally precipitate in response to sudden increases in pH (e.g., during boiling). Mn-silicate minerals will tend to dissolve in solutions undergoing cooling, whereas rhodocrosite exhibits either prograde or retrograde solubility, depending on salinity. Manganese mobilized by hydrothermal fluids may travel considerable distances until contact is ultimately made with an oxidized environment, at which point Mn-oxide minerals will precipitate.